2013
DOI: 10.1002/hyp.9870
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and canopy characteristics of two lodgepole pine stands following mountain pine beetle attack

Abstract: Abstract:Over the past decade, British Columbia (BC), has experienced the largest mountain pine beetle (MPB) outbreak on record. This study used the eddy-covariance (EC) technique to examine the impact of the MPB attack on evapotranspiration (E) and associated canopy characteristics of two lodgepole pine stands with secondary structure (trees, saplings and seedlings surviving the attack) located in central BC. MPB-06, an 85-year-old almost pure stand of pine trees, was first attacked in 2006, and by 2010,~80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…The damage to plants caused by insects, particularly during outbreaks defined by sudden and major changes in insect population, is pervasive in terrestrial ecosystems and affects not only vegetation dynamics but also carbon, nutrient, energy, and water exchanges, and even atmospheric chemistry (Landsberg and Ohmart, 1989;Hunter, 2001;Lovett et al, 2002;Kurz et al, 2008;Amiro et al, 2010;Arneth and Niinemets, 2010;Clark et al, 2010Clark et al, , 2012Stinson et al, 2011;Bowler et al, 2012;Brown et al, 2012Brown et al, , 2014Edburg et al, 2012;Hicke et al, 2012;Yang, 2012; J. Bright et al, 2013;Maness et al, 2013;Mikkelson et al, 2013a;Pugh and Gordon, 2013;Metcalfe et al, 2014;Reed et al, 2014;Seidl et al, 2014;Turcotte et al, 2014;Vanderhoof et al, 2014;Landry and Parrott, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The damage to plants caused by insects, particularly during outbreaks defined by sudden and major changes in insect population, is pervasive in terrestrial ecosystems and affects not only vegetation dynamics but also carbon, nutrient, energy, and water exchanges, and even atmospheric chemistry (Landsberg and Ohmart, 1989;Hunter, 2001;Lovett et al, 2002;Kurz et al, 2008;Amiro et al, 2010;Arneth and Niinemets, 2010;Clark et al, 2010Clark et al, , 2012Stinson et al, 2011;Bowler et al, 2012;Brown et al, 2012Brown et al, , 2014Edburg et al, 2012;Hicke et al, 2012;Yang, 2012; J. Bright et al, 2013;Maness et al, 2013;Mikkelson et al, 2013a;Pugh and Gordon, 2013;Metcalfe et al, 2014;Reed et al, 2014;Seidl et al, 2014;Turcotte et al, 2014;Vanderhoof et al, 2014;Landry and Parrott, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies pointing towards increased streamflow also broadly found evapotranspiration from the canopy decreased, leading to an increase in runoff. However, work based on observations across scales and encompassing multiple disturbances indicates that the regrowth potential for understory, such as shrubs used in this study, is high and that the regrowth is a major controlling factor for water availability and direction of change for evapotranspiration and runoff (Caldwell et al, 2016;Biederman et al, , 2015Brown et al, 2014;Pribulick et al, 2016). Moreover, ecologists project that global forest covers are expected to decline and be replaced with species and understory compositions that are more water intensive.…”
Section: Discussionmentioning
confidence: 90%
“…First, replacement of forest with shrubs leads to an increase (relative to the climate-only scenario) in the onthe-ground snow pack accumulation (Fig. 4b), a prominent feature observed in disturbed forests across North America (Boon, 2007;Zou et al, 2010;Biederman et al, 2015;Brown et al, 2014;Harpold et al, 2014). Shrubs in our VIC simulations have no canopy thus they have no mechanism to intercept snow.…”
Section: Changing Streamflow and Water Balancesmentioning
confidence: 87%
See 1 more Smart Citation
“…6). In stands killed during the first die-off wave, dense and fastgrowing stand regeneration was increasingly able to compensate for diminished evapotranspiration losses due to mature tree mortality (Brown et al, 2014). Almost a decade later, this recovery was impacted by the second wave of die-off, which hampered a rapid comeback of catchment evapotranspiration to pre-disturbance level.…”
Section: Runoff Response To Forest Disturbancementioning
confidence: 99%